Welcome :: Homework Help and Answers :: Mathskey.com

Recent Visits

    
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,433 questions

17,804 answers

1,438 comments

47,278 users

Simplify, (4a - 2b)(a + b)?

+2 votes

4a^2 - 6ab - 2b^2
4a^2 - 2ab - 2b^2
4a^2 - 8ab - 2b^2
4a^2 + 2ab - 2b^2

asked Mar 2, 2013 in BASIC MATH by chrisgirl Apprentice

4 Answers

–1 vote

(4a-2b)(a+b)
=(4a*a + 4a*b + (-2b)*a + (-2b)*b)
=(4a² + 4ab - 2ba -2b²)
=4a² + 2ab - b²

answered Mar 2, 2013 by kevin Rookie
+1 vote

By Using Foil (First Outside Inside Last) Method expression can be simplified as
(4a - 2b)(a + b)
= 4a * a + 4a * b + (-2b) * a + (-2b) * b
=4a^2 + 4ab -2ab -2b^2
=4a^2 + 2ab -2b^2

answered Mar 2, 2013 by casacop Expert
0 votes
Option D is right choice. Casacop answer is right.
answered Mar 3, 2013 by John Lyn Pupil
+1 vote

Hi
(4a-2b)(a+b)
=(4a*a + 4a*b + (-2b)*a + (-2b)*b)
=(4a² + 4ab - 2ba -2b²)
=4a² + 2ab - b²

Hope I helped :)

Source: answers.yahoo.com

answered Mar 3, 2013 by rob Pupil

Related questions

asked Nov 26, 2014 in ALGEBRA 1 by anonymous
asked Oct 2, 2014 in CALCULUS by anonymous
...